Peran Orang Tua Single Parent dalam Pembinaan Karakter Religius Anak (Studi di Desa Talang Balai Baru II Kecamatan Tanjung Raja Kabupaten Ogan Ilir) - Desi Suryati; Zainuddin; Ani Nafisah (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2025)
The role of parents is indeed crucial in shaping the personality and values of children, including in religious aspects. A study conducted in Talang Balai Baru II Village reveals an interesting phenomenon about the role of single parents in fostering their children's religious character. Although children of single parents can have good religious character, they also face significant challenges in the process. This study aims to describe how single parents play a role in fostering their children's religious character and to identify the various obstacles they encounter in the process. Using a descriptive qualitative approach, data was collected through observation, interviews, and documentation. The data was then analyzed through stages of data reduction, data presentation, and drawing conclusions. The research findings indicate that single parents in Talang Balai Baru II Village have carried out their role quite well in instilling religious character in their children. This is done through the cultivation of faith, the practice of worship, and the formation of noble morals. They also strive to be good role models, offer constructive advice, and continuously pray for their children to stay on the right path. However, there are significant challenges, such as the limited time and energy of single parents in balancing work and educating their children. In addition, emotional pressure arises from concerns about the negative influences of the social environment and technological developments, particularly those coming from peers and social media.